ANALISIS KINERJA KEUANGAN PT. JAMSOSTEK (PERSERO) KANTOR CABANG SAMARINDA - Mulyono, Edi (EKONOMIA, 2013)
EDI MULYONO, Faculty of Economics, University of 17 August 1945 Samarinda, analysis financial performance PT.Jamsostek (Persero) Samarinda branch offices, under the guidance of Father Prof.Dr.Eddy Soegiato K, SE, MM and Mr. Imam Nazaruddin Latif SE, Ak.Law No. 17 of 2003 about the finances of the State obliges the Government to draft RI report financial assessment of the level of health of the PT.Jamsostek (Persero) Samarinda Branch Office is according to the decision of the Board of Directors number: KEP/207/092004 on branch office. Equity funds adequacy ratio on smoothly experienced the pengingkatan proportion, i.e. on the fiscal year 2010 amounted to 1.4% to 1.8%, in fiscal year 2011 or experiencing an increase of 28,57%.Equity investment funds has decreased the proportion of yani on fiscal year 2010 amounted to 98.6% to 98,2% in fiscal year 2011 or decreased by 0.4%, this indicates that the proportion of equity investment funds experienced a decline from fiscal year 2010 to 2011. Pengukurn performance analysis 1. Analysis of the absorption of the 2011 budget surpasses launched by 28% due to the 13th salary, 2. Analysis of the consistency between the planning and implementation of 2011setiap year month average 97%, 3. Analysis of the achievement of output exceeds pagu from 98,32% to 99,93%, 4. Analysis of benefits in 2011 can be realised for 104,2%, 5. Analysis of performance assessment of implementation, consistency among aspects of planning and implementation, achievement of output and efficiency analysis of 78,3% 33.3% with weights and aspects of benefits for 104,2% 66,7%, with weights obtained performance in 2011 of 95,58% with the very good category. It can be concluded that the financial performance of kengukuran in PT.Jamsostek (Persero) Samarinda branch office in 2011 has an excellent financial performance.